Independence of Learning with the Concept of Self-Taught in Non-Formal Education Units in Pesantren Cikoneng, Ciparay District (YPI) - Nurul Firdaus; Dwi Novia Al Husaeni (ISLAMIKA, 2023)
The purpose of this research is to find out the role of the Cikoneng Islamic Boarding School (YPI) in creating students' independent learning, to find out what programs the Cikoneng Islamic Boarding School (YPI) has that can support the creation of students' independent learning. This study used a qualitative field research approach, with data collection techniques in the form of observation, interviews with key informants and documentation. Then to analyze the data researchers used data reduction techniques, data presentation and conclusions or verification. To determine the validity of the data, researchers used source triangulation techniques and technical triangulation. The results of this study are that all components and systems in the Cikoneng Islamic boarding school (YPI) play an important role in creating independent learning within students. For example, from the human resources, such as teachers, administrators, caretakers and leaders of Islamic boarding schools. Their presence is needed by the students, as motivators, mentors as well as their second parents at the boarding school. Then the creation of learning independence is also created from programs that have been formed by the boarding school, such as additional recitation, scientific and linguistic groups as well as rote tests and others. The Cikoneng Islamic Boarding School (YPI) program that supports the creation of independent learning for students, namely the Muhadhoroh and Munadhoroh programs at Islamic boarding schools, with this program can produce students who are independent and able to appear in society in practicing the knowledge they already having.